PWE-237 Ciclosporin in acute severe ulcerative colitis: a meta-analysis. (28th May 2012) - Krishnamoorthy, R; Abrams, K R; Guthrie, N; Samuel, S; Thomas, T
Abstract : Introduction: The efficacy of intravenous Ciclosporin in the treatment of acute severe steroid refractory ulcerative colitis is variable in several small studies. 1 2 The benefit of immunosuppression in initial responders for preventing delayed colectomy is unclear and large randomised trials are not forthcoming. The primary aim of the meta-analysis was to evaluate the efficacy of intravenous Ciclosporin in steroid refractory acute colitis. Primary end points were immediate and delayed colectomy rates. Secondary end points were delayed colectomy rates in responders on immunosuppression vs no immunosuppression. Methods: MEDLINE (1966–2011), EMBASE and PubMed databases searched using keywords, "colitis" "acute colitis, " "ciclosporin, " "cyclosporin, " "ulcerative colitis" and "fulminant colitis" from January 1965 to December 2011. Articles were selected/reviewed based on a pre-defined inclusion criteria and independently reviewed by three authors (RK, NG and TT) and data collected. Meta-analysis using random effects model was done. Results: 31 studies involving 1295 patients were included in the final analysis (692 males, average age 37.4 years, range 27–58.8 years). The average duration of colitis prior to admission (25 studies, 1062 patients) was 54 months and 660 patients (26 studies, 1148 patients) had pancolitis. The immediate colectomy rate was 23.6%, (95% CI 20% to >27.5%) and delayed colectomy 37.8% (95% CI 32.8% to 43.1%) at an average follow-up of 28.8 months. On meta-regression analysis the duration of colitis was the only confounding factor for delayed colectomy (p=0.05). On sub-group analysis, immunosuppression (Aza/6MP) in initial responders significantly reduced delayed colectomy rates by 20% (OR 0.36, 95% CI 0.61 to 0.81, p=0.014). The number need to treat to prevent one delayed colectomy was 5. There was a 13% increase in colectomy rates in the sub-group of patients (5 studies, 113 patients) who were on immunosupression (failed immunospression) prior to iv ciclosporin although this was not statistically significant (p=0.22). Conclusion: Intravenous Ciclosporin prevents immediate and delayed colectomy in 76.4% and 62% respectively. There is a non-significant increase in colectomy rates (13%) in patients who failed immunosuppression prior to Ciclosporin. Immunosuppression in initial responders significantly reduces delayed colectomy rates and should be considered unless contraindicated. Competing interests: None declared. References: 1. Cheifetz AS, et al. Ciclosporin is safe and effective in patients with severe Ulcerative Colitis. J Clin Gastroenterol 2011;45 :107–12. 2. Lichtiger S, et al. Cyclosporin in severe Ulcerative Colitis refractory to steroid therapy. N Engl J Med 1994;330 :1841–5.